2020
DOI: 10.21203/rs.3.rs-31204/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Functional Impacts of the Covid-19 Pandemic: A Rapid Review

Abstract: Background: The Covid-19 pandemic is having a severe and unprecedented impact on human functioning, due to its influence on bodily functions and structures, the activities we participate in and the environments in which we live. The aim of this rapid review is to inform health services planning and decision making, by identifying and synthesizing the potential functional impact of the Covid-19 pandemic on human health and wellbeing.Methods: This rapid review was completed within four weeks during April – May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(198 reference statements)
0
4
0
Order By: Relevance
“…[18] Together the physical and functional impacts lead to COVID-19 patients being weak, having fever, suffering from anxiety and depression, not just this they had joint pain, muscle pain, sore throat, nasal congestion, headache, loss of smell and taste and diarrhoea. [19] Less common physical symptoms include discoloration of toes or fingers while the serious physical and functional symptoms include chest pain or pressure, difficulty breathing, loss of speech and movement. [8] The main motive of our study was to assess the functional impacts of the patients infected with COVID-19 admitted in the hospitals of Islamabad and Rawalpin-According to the FSS-ICU scale, 6.0% of the participants were completely reliant on their caregivers/ nurses, 9.8% required maximum assistance, 17.5% required moderate assistance, 14.8% required minimal assistance, 13.1% required supervision to complete their tasks, and 15.3% required assistance (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…[18] Together the physical and functional impacts lead to COVID-19 patients being weak, having fever, suffering from anxiety and depression, not just this they had joint pain, muscle pain, sore throat, nasal congestion, headache, loss of smell and taste and diarrhoea. [19] Less common physical symptoms include discoloration of toes or fingers while the serious physical and functional symptoms include chest pain or pressure, difficulty breathing, loss of speech and movement. [8] The main motive of our study was to assess the functional impacts of the patients infected with COVID-19 admitted in the hospitals of Islamabad and Rawalpin-According to the FSS-ICU scale, 6.0% of the participants were completely reliant on their caregivers/ nurses, 9.8% required maximum assistance, 17.5% required moderate assistance, 14.8% required minimal assistance, 13.1% required supervision to complete their tasks, and 15.3% required assistance (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The pandemic and post-pandemic periods have substantiated how consequential adequate therapy can be for the physical and mental impairment of the patients, especially the individuals affected by the possible long-term adverse effects of the acute form of the SARS-CoV-2 infection. Consequently, emphasis should be placed on more holistic and multidisciplinary methodologies for the collation of information to ameliorate the diagnoses of the adverse effects associated with the disease [8,9]. Muscle weakness is one of the more notable symptoms, which is exhibited in the acute form of COVID-19 that compromises the respiratory musculature [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Beckman observed that the inability to continue daily routines and practice usual habits and work activities often leads to low levels of energy, chaos, and emotional exhaustion [ 18 ]. As might be expected, many of the reports in the literature emerging from the COVID-19 pandemic in general focus on negative effects, such as despair, helplessness, and hopelessness and apply various tools and questionnaires to measure these negative effects [ 3 , 19 ]. To the best of our knowledge, this is the first study that specifically explored the association of COVID-19 lockdown with hope.…”
Section: Discussionmentioning
confidence: 99%